Comparative Analysis of PPPOE and SSTP Performance in Microtic(Analisis Perbandingan Kinerja PPPOE dan SSTP Pada Mikrotik) - Andika Agus Slameto; Rahmat Hidayat (Jurnal KomtekInfo, 2019)
Tunneling is the process of packaging data sent by other protocols in a network. Point to point over Ethernet (PPPOE) andSecure Socket Tunneling Protocol (SSTP) are protocols that function or are designed to carry out tunneling processes. Datasecurity in this case is a top priority, with the encapsulation and authentication process making tunnels one of the many waysto secure data in a network. Besides security, network performance is something that must be considered in providing goodservices. In the process of testing the performance of PPPOE and SSTP using the Quality of Service method, it can beconcluded that SSTP is better in the parameters of Througput, Delay, and Jitter while PPPOE is better in Packet Loss. In thesecurity testing phase, both protocols have encapsulated data packets sent over an http-based web.